About a Rare Association Between Vulvar Dowling Degos Disease and HS - Dupont M; Parent M; Vanhooteghem O (Dove Medical Press, 2023)
Manon Dupont,1 Muriel Parent,2 Olivier Vanhooteghem1 1Dermatology Department, CHU UCL Namur, Site Sainte Elisabeth, Namur, 5000, Belgium; 2Department of Pathology, Institute of Pathology and Genetics (IPG), Gosselies, 6041, BelgiumCorrespondence: Olivier Vanhooteghem, Email ovanhooteghem@hotmail.comAbstract: Dowling Degos disease (DDD) is a rare genodermatosis that manifests itself as acquired, reticulated hyperpigmentation of the folds. We report the case of a 45-year-old woman who presented since the age of 30 with hyperpigmented macules of reticulated appearance of vulvar, perianal and bilateral axillary location associated with hidradenitis suppurativa (HS) at Hurley stage 2 of later onset. DDD is classically described in the flexural folds and, to our knowledge; less than a dozen cases of vulvar location are published in the literature. We postulate that DDD is responsible for the development of HS in susceptible patients. Indeed, this association seems to be explained by a common pathophysiological mechanism, targeting the Notch signalling pathway, involved in the proliferation and differentiation of epidermal cells that can induce the development of HS. DDD should be considered as a comorbid factor of HS.Keywords: hidradenitis suppurativa, Dowling Degos, vulvar, hyperpigmentation, comorbidities